PENGARUH EKSTRAK DAUN KASTURI TERHADAP KADAR LIMFOSIT MENCIT JANTAN (Mus musculus) YANG DIPAPAR SINAR-X RADIOGRAFI PERIAPIKAL - Syifa Ennisa; Didit Aspriyanto; Irham Taufiqurrahman (Dentin, 2022)
ABSTRACTBackground: Periapical radiographic X-ray exposure can cause blood cell damage, such as lymphocyte damage. Direct damage occurs when it attacks the DNA and RNA of cells. Indirect damage occurs through the formation of free radicals. One of the natural antioxidants that can be used is kasturi leaves. Kasturi leaf extract contains active ingredients such as flavonoids, phenols, alkaloids, terpenoids, and saponins that can inhibit free radical activity. Objective: To measure and analyze the effect of kasturi leaf extract on the increase in lymphocytes levels of male mice exposed to x-ray periapical radiographs. Methods: This study used a true experimental method with a post test only design with a control group design. The samples used were 20 male mice aged 3-4 months with 20-25 grams bodyweight. Mice were divided into 5 groups, each group consisted of 4 mice. Mice were given kasturi leaf extract and exposed to x-ray periapical radiographs. Mice lymphocytes levels were measured automatically using a hematology analyzer. Results: Lymphocyte levels in P1 group = 3,400 x 103/µL, P2 group = 5,725 x 103/µL, P3 group = 7,825 x 103/µL, P4 group = 9,750 x 103/µL, and P5 group = 5,375 x 103/µL. Conclusion: Differences in lymphocyte levels were influenced by antioxidants from kasturi leaf extract and large differences in the radiation dose received. Keywords :   Kasturi leaf extract, Lymphocytes, Periapical radiography ABSTRAKLatar Belakang: Paparan sinar-X radiografi periapikal dapat menyebabkan kerusakan sel darah, seperti kerusakan limfosit. Kerusakan langsung terjadi apabila mengenai DNA dan RNA sel. Kerusakan tidak langsung terjadi melalui pembentukan radikal bebas. Salah satu antioksidan alami yang dapat digunakan adalah daun kasturi. Ekstrak daun kasturi mengandung bahan aktif seperti flavonoid, fenol, alkaloid, terpenoid, dan saponin yang dapat menghambat aktivitas radikal bebas. Tujuan: Untuk mengukur dan menganalisis pengaruh ekstrak daun kasturi terhadap peningkatan kadar limfosit mencit jantan yang dipapar sinar-X radiografi periapikal. Metode: True experimental dengan post test only with control group design. Sampel yang digunakan adalah 20 ekor mencit jantan berusia 3-4 bulan dengan berat badan 20-25 gram. Mencit dibagi menjadi 5 kelompok, masing-masing kelompok berjumlah 4 ekor mencit. Mencit diberi ekstrak daun kasturi dan dipapar sinar-X radiografi periapikal. Kadar limfosit mencit diukur secara automatis menggunakan hematology analyzer. Hasil: Kadar limfosit kelompok P1 = 3,400 x 103/µL, kelompok P2 = 5,725 x 103/µL, kelompok P3 = 7,825 x 103/µL, kelompok P4 = 9,750 x 103/µL, dan kelompok P5 = 5,375 x 103/µL. Kesimpulan: Perbedaan kadar limfosit terjadi karena pengaruh antioksidan ekstrak daun kasturi dan perbedaan besar dosis radiasi yang diterima.                                           Kata kunci:  Ekstrak daun kasturi, Limfosit, Radiografi periapikal